Pengembangan LKPD berbasis PBL untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas VIII pada Materi Sistem Persamaan Linear Dua Variabel - Aflahul Ma'wa; Hapipi Hapipi; Muhammad Turmuzi; Syahrul Azmi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
The purpose of this study was to develop student worksheets based on PBL (Problem Based Learning) to improve the problem-solving abilities of class VIII students at MTs Hikmatusysyarief NW Salut Narmada for the 2020-2021 school year on two-variable linear equation systems. PBL-based LKPD (Problem Based Learning) is an LKPD that is arranged based on the phases of the PBL learning model. The development of this product aims to overcome the weaknesses in the teaching and learning process and overcome the weaknesses of students' problem-solving abilities. The research methodology used in developing PBL-based LKPD is 4D (Define, Design, Development, and Dissemination). Data collection techniques using interview guidelines and questionnaires. The result of the research is a product in the form of LKPD based on PBL (Problem Based Learning) on ​​the material of a two-variable linear equation system. The product has been declared valid with very good criteria by two validators. Based on the results of a limited trial on the use of the developed product, it is known that the PBL-based LKPD can improve the problem-solving ability of class VIII students of MTs Hikmatusysyarief NW Salut Narmada.